Physical rehabilitation modulates microRNAs involved in multiple sclerosis: a case report. Issue 12 (2nd November 2017) - Vallelunga, Annamaria; Berlingieri, Carmine; Ragusa, Marco; Purrello, Michele; Stabile, Maria Rosaria; Calabrese, Maria Consiglia; Morales‐Medina, Julio Cesar; Palmieri, Beniamino; Iannitti, Tommaso
Key Clinical Message: This study shows that neuromuscular taping improves gait, balance, pain and ability to walk and conduct daily activities in a multiple sclerosis patient. It is the first study to identify a panel of miRNAs modulated throughout rehabilitation using neuromuscular taping in a multiple sclerosis patient. Abstract : This study shows that neuromuscular taping improves gait, balance, pain, ability to walk and conduct daily activities in a multiple sclerosis patient. It is the first study to identify a panel of miRNAs modulated throughout rehabilitation using neuromuscular taping in a multiple sclerosis patient.